Use storytelling to show how your institution is distinct, encourage students to enroll. Issue 10 (10th June 2021) - Hope, Joan
Abstract : At one time, colleges and universities benefited from their prestige and from the attitude that people need a degree to be successful, said Joseph Lapin, Vice President of Marketing and Brand Strategy at Archer Education. But there's been a major shift, Lapin added.